Hubungan Komunikasi Pelayanan Publik dengan Kepuasan Nasabah - Habi Rahman Kamel; Aning Sofyan (Bandung Conference Series: Communication Management, 2022)
Abstract. The main activity of communication activities is the most important thing every activity service provided by a Bank. Communication activities able to provide the best services for public spaces and good service , and the public trust for the banks and encourage gratification for that customers that made his they show their loyalty of the Bank Nagari West Sumatra the Branch of Solok. Research objectives know the relationship between service excellence, the ability to communicate, professional, integrity communication public service by satisfaction customers, attitude respect communication public service by satisfaction customers. A method of correlational aims to research about ties in one factor relating to variation to other factors. Population used in this research even all customers Bank Nagari Branches Solok with the total sample obtained using formulas were 96 respondents. The data in the survey, interview, observation and the study of literature. Drawing conclusions: the existence of the the strong relationship between service (significant comprise, the ability to communicate, professionalism,theintegrityof communication public service by customer satisfaction, respect attitude communication public services with satisfaction the customers Bank Nagari West Sumatra the Branch of Solok . Abstrak. Kegiatan komunikasi merupakan kegiatan utama yang terpenting dalam setiap pelaksanaan kegiatan pelayanan yang diberikan oleh bank. Kegiatan komunikasi mampu memberikan pelayanan yang terbaik dan berkualitas bagi publiknya, sehingga melahirkan kepercayaan publik bagi bank dan mendorong kepuasan bagi para nasabah sehingga menjadikan mereka loyal terhadap Bank Nagari Sumatera Barat Cabang Solok. Tujuan penelitian mengetahui hubungan antara service excellence, kemampuankomunikasi,profesionalisme, integritas komunikasi pelayanan publik dengan kepuasan nasabah, sikap respect komunikasi pelayanan publik dengan kepuasan nasabah. Metode korelasional bertujuan meneliti sejauhmana hubungan pada satu faktor berkaitan dengan variasi pada faktor lain. Populasi digunakan dalam penelitian ini yaitu seluruh nasabah Bank Nagari Cabang Solok dengan jumlah sampel yang didapatkan menggunakan rumus berjumlah 96 responden. Pengambilan data berupa penyebaran angket, wawancara, observasi dan studi kepustakaan. Simpulan: Adanya hubungan kuat (signifikan) antara service excellence, kemampuankomunikasi, profesionalisme, integritas komunikasi pelayanan publik dengan kepuasan nasabah, sikap respect komunikasi pelayanan publik dengan kepuasan nasabah Bank Nagari Sumatera Barat Cabang Solok.